Defining locally advanced basal cell carcinoma and integrating smoothened inhibitors into clinical practice. Issue 2 (March 2016) - Khoo, Andre B.S.; Ali, Faisal R.; Lear, John T.
Abstract : Purpose of review: We summarize the concept of a locally advanced basal cell carcinoma (laBCC) and present the current consensus definition. We also review the key pieces of primary research undertaken in the past year and how these affect the use of smoothened inhibitors in a clinical setting. Recent findings: Medium term follow-up (30 months) of patients treated with vismodegib shows an improvement in response rates for patients with laBCC. The safety profile of vismodegib demonstrated in the original ERIVANCE study has been replicated in a larger patient cohort in a repeat study. Sonidegib is a new smoothened inhibitor currently under investigation for treatment of laBCC, which demonstrates a comparable safety profile to vismodegib. The side-effects of smoothened inhibitors appear related to both dose and duration of treatment. The durability of response to vismodegib is uncertain, but has been observed to last for over a year following discontinuation of treatment. Summary: The understanding of the efficacy and safety of vismodegib has improved since its introduction in 2012. A broadening evidence base supports its use as a valid treatment for laBCC. However, questions remain as to how to integrate its use into existing pathways for treating laBCC and its long-term efficacy.